Commitment and training: professionalization narratives in the implementation of social and emotional learning policies in Chilean schools - Bonhomme, Alfonso; Rojas, María Teresa (Frontiers in Education, 2024)
Since the beginning of the pandemic, the discourse on mental health has strongly permeated educational spaces. This is evidenced by the proliferation of policies and initiatives related to Social and Emotional Learning (SEL), which urgently emphasize socio-emotional development and the psychological and subjective well-being of students. This phenomenon makes it necessary to study how professionals should take responsibility and implement a series of practices to respond to these initiatives and policies, many of which are improvised and poorly understood by the community. The aim of this article is to analyze the narratives of professionalization produced by educational agents responsible for implementing SEL policies in Chilean schools. For this purpose, in-depth narrative interviews were conducted with 12 primary education actors, including principals, educational psychologists, school climate coordinators, and homeroom teachers. The participants were selected from different types of educational institutions, including public schools, subsidized private schools, and private schools. Through an inductive Reflexive Thematic Analysis (RTA), two main themes were identified that articulate the professional experience of implementing SEL policies among the interviewees: (1) commitment to SEL and the (dis)continuities between institutions and personal efforts, and (2) initial and ongoing training for the implementation of SEL. Moreover, from these two proposed themes, various sub-themes emerged, classified according to the types of professionals interviewed and the complexities associated with the types of schools where they work. These sub-themes demonstrate how discourses on the emotional dimension and SEL in schools translate into concrete implications, both subjective and material, regarding the daily work of the interviewees. Finally, the article discusses the complexity arising from the narrative differences among professionals, particularly in terms of their initial and ongoing training, as well as the importance of shared commitments among communities in recognizing the work carried out by these professionals.